MAYBE Initial complexity problem: 1: T: (1, 1) f1(a, b) -> f0(a, b) (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 A polynomial rank function with Pol(f0) = V_1 and size complexities S("f0(a, b) -> f0(a + b, b) [ a >= 1 /\\ 0 >= b + 1 ]", 0-0) = a + b S("f0(a, b) -> f0(a + b, b) [ a >= 1 /\\ 0 >= b + 1 ]", 0-1) = b S("f0(a, b) -> f0(a + b, b) [ a >= 1 /\\ b >= 1 ]", 0-0) = ? S("f0(a, b) -> f0(a + b, b) [ a >= 1 /\\ b >= 1 ]", 0-1) = b S("f1(a, b) -> f0(a, b)", 0-0) = a S("f1(a, b) -> f0(a, b)", 0-1) = b orients the transition f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] weakly and the transition f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] strictly and produces the following problem: 2: T: (1, 1) f1(a, b) -> f0(a, b) (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a, b) with all transitions in problem 2, the following new transitions are obtained: f1(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] We thus obtain the following problem: 3: T: (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] with all transitions in problem 3, the following new transition is obtained: f1(a, b) -> f0(a + 2*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 ] We thus obtain the following problem: 4: T: (1, 3) f1(a, b) -> f0(a + 2*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 2*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 ] with all transitions in problem 4, the following new transition is obtained: f1(a, b) -> f0(a + 3*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 ] We thus obtain the following problem: 5: T: (1, 4) f1(a, b) -> f0(a + 3*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 3*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 ] with all transitions in problem 5, the following new transition is obtained: f1(a, b) -> f0(a + 4*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 ] We thus obtain the following problem: 6: T: (1, 5) f1(a, b) -> f0(a + 4*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 4*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 ] with all transitions in problem 6, the following new transition is obtained: f1(a, b) -> f0(a + 5*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 ] We thus obtain the following problem: 7: T: (1, 6) f1(a, b) -> f0(a + 5*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 5*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 ] with all transitions in problem 7, the following new transition is obtained: f1(a, b) -> f0(a + 6*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 ] We thus obtain the following problem: 8: T: (1, 7) f1(a, b) -> f0(a + 6*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 6*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 ] with all transitions in problem 8, the following new transition is obtained: f1(a, b) -> f0(a + 7*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 ] We thus obtain the following problem: 9: T: (1, 8) f1(a, b) -> f0(a + 7*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 7*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 ] with all transitions in problem 9, the following new transition is obtained: f1(a, b) -> f0(a + 8*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 ] We thus obtain the following problem: 10: T: (1, 9) f1(a, b) -> f0(a + 8*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 8*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 ] with all transitions in problem 10, the following new transition is obtained: f1(a, b) -> f0(a + 9*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 ] We thus obtain the following problem: 11: T: (1, 10) f1(a, b) -> f0(a + 9*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 9*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 ] with all transitions in problem 11, the following new transition is obtained: f1(a, b) -> f0(a + 10*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 ] We thus obtain the following problem: 12: T: (1, 11) f1(a, b) -> f0(a + 10*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 10*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 ] with all transitions in problem 12, the following new transition is obtained: f1(a, b) -> f0(a + 11*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 ] We thus obtain the following problem: 13: T: (1, 12) f1(a, b) -> f0(a + 11*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 11*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 ] with all transitions in problem 13, the following new transition is obtained: f1(a, b) -> f0(a + 12*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 ] We thus obtain the following problem: 14: T: (1, 13) f1(a, b) -> f0(a + 12*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 12*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 ] with all transitions in problem 14, the following new transition is obtained: f1(a, b) -> f0(a + 13*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 ] We thus obtain the following problem: 15: T: (1, 14) f1(a, b) -> f0(a + 13*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 13*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 ] with all transitions in problem 15, the following new transition is obtained: f1(a, b) -> f0(a + 14*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 /\ a + 13*b >= 1 ] We thus obtain the following problem: 16: T: (1, 15) f1(a, b) -> f0(a + 14*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 /\ a + 13*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 By chaining the transition f1(a, b) -> f0(a + 14*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 /\ a + 13*b >= 1 ] with all transitions in problem 16, the following new transition is obtained: f1(a, b) -> f0(a + 15*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 /\ a + 13*b >= 1 /\ a + 14*b >= 1 ] We thus obtain the following problem: 17: T: (1, 16) f1(a, b) -> f0(a + 15*b, b) [ a >= 1 /\ 0 >= b + 1 /\ a + b >= 1 /\ a + 2*b >= 1 /\ a + 3*b >= 1 /\ a + 4*b >= 1 /\ a + 5*b >= 1 /\ a + 6*b >= 1 /\ a + 7*b >= 1 /\ a + 8*b >= 1 /\ a + 9*b >= 1 /\ a + 10*b >= 1 /\ a + 11*b >= 1 /\ a + 12*b >= 1 /\ a + 13*b >= 1 /\ a + 14*b >= 1 ] (1, 2) f1(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (?, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ b >= 1 ] (a, 1) f0(a, b) -> f0(a + b, b) [ a >= 1 /\ 0 >= b + 1 ] start location: f1 leaf cost: 0 Complexity upper bound ? Time: 1.630 sec (SMT: 1.537 sec)